Non-Verbal Communication in the Tom and Jerry Film - Ariyati, Yumi; Catherine, Sarkissian (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The purpose of this writing is to delve deeper into nonverbal and verbal communication in the cartoon film